If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -56 = 74 + 10x Solving -56 = 74 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -56 + -10x = 74 + 10x + -10x Combine like terms: 10x + -10x = 0 -56 + -10x = 74 + 0 -56 + -10x = 74 Add '56' to each side of the equation. -56 + 56 + -10x = 74 + 56 Combine like terms: -56 + 56 = 0 0 + -10x = 74 + 56 -10x = 74 + 56 Combine like terms: 74 + 56 = 130 -10x = 130 Divide each side by '-10'. x = -13 Simplifying x = -13
| -3(2x-2)=24 | | 8t-10-2t=-6+10+9t | | 6y+3x=22 | | x+10(x+1)+5=550 | | 2y+4x=12.50 | | a^2+6a=7 | | -(5-3x)+x=4 | | 2r^3+8r^2+6r=0 | | -3.4x=36 | | x+64=x+59 | | x+64+x+59=75 | | -53=90-11x | | x+64+x+59+75=180 | | 18+6g=2(4c+5) | | 5.9x-1=12.7+6.2 | | -6-3(2k+4)=14 | | 3(a-4)=-21 | | 3y^2+3y-18=0 | | 12r-9=6r+18 | | 15=a+24 | | 7m-17=6 | | -28=p+2 | | 5m-2=2m | | 4x+8=15.4 | | 2x+4+x=3(x-2) | | 4(2x-3)=5x-6 | | 8x+3-4x=5+x | | -5c-12+(-5c)=8 | | 43+8x=187 | | t-9=24 | | 4.7w+11.8(1-w)=10 | | 4(m-2)=-12 |